UMPSA, SIT strengthen strategic cooperation in academics, research, and internationalization - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2024)
PEKAN, 18 January 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has bolstered bilateral relations and strategic academic and research collaboration with Shibaura Institute of Technology (SIT), Japan, through the signing of a Memorandum of Understanding (MoU).